IMPLEMENTASI NILAI-NILAI KONSEP “TRITANGTU SUNDA” SEBAGAI METODELOGI PENCIPTAAN TEATERKONTEMPORER - Tatang Rusmana (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
Tritangtu Sunda is a living philosophy of traditional Sundanese people including in Bandung regency. Having three important meanings of the division of the world, the three worlds are Buana Nyungcung (Upper world), Buana Larang (Underworld), and Buana Pancatengah (Middle world). The Sundanese Tritangtu is the perspective of the unification of the three worlds in peasant life. The union is the marriage of Buana Nyungcung with Buana Larang, and Buana Pancatengah is the one that unites it. The concept of the Sundanese Tritangtu influences the art of Wawacan speech that is commonly displayed into the art of Beluk. Wawacan is what helped shape the collective minds of the Sundanese people. Wawacan which is the source of dissertation research is “Wawacan Nata Sukma” written anonymously by Banjaran society, Regency of Bandung in 1833 AD (19th century) during “Cultuurstelsel” to grow coffee in Pangalengan. Sunda Tritangtu will function as a method of theater- based theater of contemporary theater. This research uses Isser’s reception theory, to actualize the work in different ways. There is no single correct interpretation (Culler, 2003). George Land’s approach of transformation theory, defined as a new creation or a change to a new form both function and structure. “To transform”, creating a new, unprecedented creation, transformation can mean a change of “mindset”. The research method used Schechner (2002) and mise en scene method formulated by Patrice Pavis.